Highly Sensitive In Vivo Imaging of Bacterial Infections with a Hydrophilicity‐Switching, Self‐Immobilizing, Near‐Infrared Fluorogenic β‐Lactamase Probe Enriched within Bacteria - Fangfang Chen; Yuyao Li; Yan Peng; Yifan Zhu; Gao He; Zhengwei Zhang; Hexin Xie (Advanced Science)
Abstract The emergence of antibiotic resistance, particularly bacterial resistance to β‐lactam antibiotics, the most widely prescribed therapeutic agents for infectious diseases, poses a significant threat to public health worldwide. The discovery of effective therapies against antibiotic‐resistant pathogens has become an urgent need, necessitating innovative approaches to accelerate the identification and development of novel antibacterial agents. On the other hand, the expression of the β‐lactam‐hydrolyzing enzyme (β‐lactamase), the major cause of bacterial resistance to β‐lactam antibiotics, provides a distinctive opportunity to visualize bacterial infection, evaluate the efficacy of existing antibiotics, screen for novel antibacterial agents, and optimize drug dosing regimens in live animals. Herein, a hydrophilicity‐switching, self‐immobilizing, near‐Infrared fluorogenic β‐lactamase probe for the highly sensitive imaging of bacterial infection in live mice is reported. This probe, in addition to a significant increase in fluorescence upon selective hydrolysis by β‐lactamases as conventional β‐lactamase probes, also massively enriches within β‐lactamase‐expressing bacteria (over 1500‐folds compared to the incubation medium), which renders excellent sensitivity in the imaging of bacterial infections in living animals. This agent has proven to enable the assessment of antibiotic therapeutic efficacy and potency of β‐lactamase inhibitors in living animals in a non‐invasive and much more convenient manner.